The role of the CIAT Outreach Program in the varietal improvement of cassava in the Philippines - Obordo, RA (International Center for Tropical Agriculture, 1978)
The objectives of the Centro Internacional de Agricultura Tropical (CIAT) are described in detail. The principal targets of the Outreach Program are then listed: (1) To provide a bridge between the international cassava centers and Asian countries so that the new technology can be evaluated, modified and disseminated. (2) To backstop the efforts of sponsoring agencies in developing and strengthening cassava national programs in Asia. The exchange of cassava propagation material that exists between th, CIAT and the countries participating in the Outreach Program is analyzed. Yields obtained from cv. and hybrids evaluated in Asia and previously selected at CIAT are included. (CIAT)